2013
DOI: 10.18052/www.scipress.com/ilcpa.5.96
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of Selected Quality Parameters of the Swimming Pools Port in Szczecin

Abstract: To estimate differentiation of water chemistry in reservoirs of swimming pools port in Szczecin, in time of 2004 -2008. In arbitrary appointed times 5 physical and chemical indicators of water quality were determined to evaluate general status and water condition -temperature, pH, NO 3 -, PO 4 3-, P tot. . Port of Szczecin is located on the Oder river and its right shoulder Regalicy. Is located in the western part of the port of Szczecin, in the northern part of the Valley of the lower Oder river on May. The p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2013
2013
2013
2013

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 2 publications
0
8
0
Order By: Relevance
“…In the present investigation it was observed that the pH of collected effluents was found to vary in the range of 8.05 in the month of April to maximum of 10.59 in the month of January. During major assessment period, the pH values recorded were above the permissible pH range of 5.5 to 9.0 as set for inland surface water subjected to pollution load [18][19][20][21][22][23][24][25][26][27][28]. The conductivity values recorded was found to vary from minimum of 7168 µmhos/cm in the month of October to maximum of 29800 µmhos/cm in the month of September.…”
Section: Volume 22mentioning
confidence: 99%
“…In the present investigation it was observed that the pH of collected effluents was found to vary in the range of 8.05 in the month of April to maximum of 10.59 in the month of January. During major assessment period, the pH values recorded were above the permissible pH range of 5.5 to 9.0 as set for inland surface water subjected to pollution load [18][19][20][21][22][23][24][25][26][27][28]. The conductivity values recorded was found to vary from minimum of 7168 µmhos/cm in the month of October to maximum of 29800 µmhos/cm in the month of September.…”
Section: Volume 22mentioning
confidence: 99%
“…In the present investigation it was observed that the pH of collected effluents was found to vary in the range of 7.80 in the month of February to maximum of 12.54 in the month of October. During major assessment period, the pH values recorded were above the permissible pH range of 5.5 to 9.0 as set for inland surface water subjected to pollution load [33][34][35][36][37][38][39][40][41][42][43].…”
Section: International Letters Of Chemistry Physics and Astronomy Vomentioning
confidence: 99%
“…It is important here to note that the permissible pH range of inland surface water subjected to pollution load is 5.5 to 9.0 [24][25][26][27][28][29]. The conductivity of the industrial waste water effluent was found to vary in the range of 4949 µmhos/cm in the month of October to 25067 µmhos/cm in the month of July.…”
Section: Physico-chemical Parametersmentioning
confidence: 99%